Residents’ preference of rooftop garden as alternative space for promoting urban agriculture in high-rise buildings - Jafari, Neda (2015)
Nowadays, many cities in many countries are trying to enhance sustainability and increasing agriculture in urban area. Urban agriculture growing up to develop environmentally friendly construction and are often built on previously unused lots, increasing the beauty and value of the neighbourhood. Urban agriculture is also fundamental on including ecological, cultural, recreational and aesthetic concerns, related to the landscape. Lack of appropriate land for urban agricultural is a main argument for promoting agricultural intensification at high-rise building. Rooftop garden on high-rise buildings are potential space to promote urban agriculture. The objective of this research is to investigate possibility for rooftop garden as an alternative space for promoting urban agriculture in high-rise building. The quantitative method of survey with questionnaire of resident’s condominium opinions has been selected for this study and the research has focused two case study which, include of (1) The Heritage condominium on Selangor and (2) Sri Putramas 2 condominium in Kuala Lumpur in Malaysia. Furthermore, the survey results have shown lead towards recognition to promoting the usage of urban agriculture at the rooftop garden in residential high-rise building. In addition, results illustrate that the majority of respondents were strongly agree with use of urban agriculture at roof of their condominium. The study has finalized that the results can further expand to promote urban agriculture on the rooftop. In conclusion, the study has contributed that use of urban agriculture encourages people to use rooftop garden which promotes sustainability of the buildings. Finally, urban agriculture space following residential space, are brought to vertical style introducing urban agriculture at rooftop gardens.